Children show limited movement repertoire when learning a novel motor skill. Issue 4 (27th September 2017) - Lee, Mei‐Hua; Farshchiansadegh, Ali; Ranganathan, Rajiv
Abstract: Examining age differences in motor learning using real‐world tasks is often problematic due to task novelty and biomechanical confounds. Here, we investigated how children and adults acquire a novel motor skill in a virtual environment. Participants of three different age groups (9‐year‐olds, 12‐year‐olds, and adults) learned to use their upper body movements to control a cursor on a computer screen. Results showed that 9‐year‐old and 12‐year‐old children showed poorer ability to control the cursor at the end of practice. Critically, when we investigated the movement coordination, we found that the lower task performance of children was associated with limited exploration of their movement repertoire. These results reveal the critical role of motor exploration in understanding developmental differences in motor learning. Abstract : We examined developmental differences in motor learning using a novel body‐machine interface paradigm that minimized biomechanical differences. We found that children showed poorer performance compared to adults, and had limited motor exploration.